Search for third-generation scalar leptoquarks decaying to a top quark and a tau lepton at root s=13 TeV - Sirunyan, A.M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Link, 2018)
A search for pair production of heavy scalar leptoquarks (LQs), each decaying into a top quark and a τ lepton, is presented. The search considers final states with an electron or a muon, one or two τ leptons that decayed to hadrons, and additional jets. The data were collected in 2016 in proton–proton collisions at √s = 13 TeV with the CMS detector at the LHC, and correspond to an integrated luminosity of 35.9 fb−1. No evidence for pair production of LQs is found. Assuming a branching fraction of unity for the decay LQ → tτ , upper limits on the production cross section are set as a function of LQ mass, excluding masses below 900 GeV at 95% confidence level. These results provide the most stringent limits to date on the production of scalar LQs that decay to a top quark and a τ lepton.